Teachers and Parents Perceptions of the 9-Year Compulsory Education Policy in Indonesia - Irawan, M. Ferry; Bella, Sinta; Alia Latifah (Yayasan Insan Mulia Bima, 2024)
The Nine-Year Compulsory Education Policy in Indonesia aims to enhance access to and quality of basic education for all school-aged children. This study aims to analyze the perceptions of teachers and parents regarding this policy and to identify the factors influencing their views. The research methodology employed includes both quantitative and qualitative approaches. Data were collected through questionnaires and in-depth interviews with teachers and parents in several regions of Indonesia. The analysis techniques used include frequency distribution, percentages and averages to describe teachers' and parents' perceptions of the 9 Year Compulsory Education policy. The results indicate that the majority of teachers and parents support this policy, despite some challenges in its implementation. Factors such as economic conditions, accessibility to education, and the quality of educational facilities influence their perceptions. The recommendations from this study include increased policy socialization, provision of adequate educational facilities, and enhancement of teacher competencies.